Childrearing Beliefs and Practices for Learning as Determined in the Context of Shared Caregiving among Chinese Heritage Families with Low-Income in the US - Li, Lok-Wah. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Christine McWayne.; Committee: Jayanthi Mistry, Cindy Liu, and Xuan Li.; Keywords: Developmental psychology, Early childhood education, and Educational psychology.